Progress in Health Education for Schizophrenia in China - Hou Yongmei (Recent Updates in Disease and Health Research Vol. 9, 2024)
Background and Implication: According to relevant data, the incidence rate of schizophrenia in China is about 6.55%, which has seriously affected the physical and mental health of patients and brought a heavy burden to their families and even society. According to relevant surveys, most patients with schizophrenia will relapse within a 2-year recovery period after clinical treatment. The main reason for the recurrence of the patient’s condition is non-compliance with treatment, such as discontinuing medication. Health education can enhance patients’ awareness of diseases, encourage them to consciously adopt behaviors and lifestyles that are beneficial to their own health, and enhance their treatment and nursing compliance. Objective: To summarize the health education methods for schizophrenia in China in the past 10 years. Methods: Relevant literature was reviewed and organized, and health education methods for schizophrenia in China were analyzed. Results: From the perspective of the target audience, health education for schizophrenia in China is mainly divided into three categories, namely those aimed at patients, those aimed at caregivers, and those aimed at patient families; From the perspective of time length, it can be divided into short-term education and medium to short-term education; From the theoretical perspective, it can be divided into the following 3 categories, namely those based on educational theory, those based on psychological theory, and those based on nursing theory. Conclusion: The implementation methods of health education for schizophrenia tend to be diversified and specialized, but their standardization and scientificity need to be improved, and the depth and breadth need to be expanded.